Interview of Benjamin Remington by Brian Shoemaker - Remington, Benjamin (Byrd Polar Research Center Archival Program, 2006)
Vladimir Ivonovich Rostogoyev (Russian meteorologist) p. 5, 16 Lieske p. 10 Jose Alvarez (Argentine Navy) p. 5, 10 Bill Morland (the Weather Central Group) p. 5 Bert Crary (glaciologist; the Chief Scientist in the Antarctic in 1957) p. 5, 6 Blacky Bennett (glaciologist) p. 5 Bill Comby (glaciologist) p. 5 Bill Boyd (Univ. of Virginia glaciologist) p. 5 Ben Harlin p. 6 Bill Moreland p. 6 Kiel, a D8 driver who died in an accident falling in a crevasse (The Kiel Field is named after him). P. 8, 9 Paul Dalrymple (microbiologist) p. 14, 15, 22, 30, 36, 42 Prof. Hoinkes from Innsbruck p. 16 Joe Farnham (who reported the thinning of ozone layer for the first time in 1969) p. 24 Fred Mayeda p. 32 Clarence McKenny p. 32 Julian Posey p. 32 Sutton p. 10, 32 Dr. Sidney Tolchin p. 34, 41, 45 Don Kitchen p. 34, 35 Red Bauhs (National Bureau of Standards) p. 35, 36, 38 Kirby Hunsen (carried the snow mine measuring project in 1958) p. 36 Lieutenant Tuck p. 50 Paul Siple p. 30 Ed Flowers (meteorologist) p. 30 Edward Fremouw (scientist) p. 31, 36, 37 Tom Smith (Navy electronic technician) p. 11, 41 Jules Madey (Ham operator in New Jersey who communicated with the Remington group) p. 42 Barry Goldwater p.43 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Benjamin_Remington_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Benjamin_Remington_2.mp3 Benjamin Remington was a meteorologist on Operation Deepfreeze II (January through December 1957) and also during IGY (International Geophysical Year) 1958-1959. Remington was one of the first civilians in Little America V. There were 18 to 20 civilians in the group including a Russian observer, Vladimir Rostogoyev and Jose Alvarez from the Argentine Navy. The Remington group left mid-December from Little America over to McMurdo and then to Christchurch. From Christchurch Remington flew directly to North Carolina. There were four meteorological researchers in total, including Remington: ...